2012
DOI: 10.3109/13880209.2012.716853
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects ofAlpinia katsumadaiagainst experimental ischemic damage via control of oxidative stress

Abstract: Won (2013) Neuroprotective effects of Alpiniakatsumadai against experimental ischemic damage via control of oxidative stress,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…Some papers have shown that the treatment of exogenous Trx increases expressions of both SOD2 mRNA and its protein level in epithelial cells of the human lens and in microvascular endothelial cells in the human lung . Furthermore, we recently reported that the maintenance or increase of endogenous SODs was closely related with protective effects against ischemia‐induced neuronal death in the gerbil hippocampus . With these findings, therefore, we strongly suggest that the enhanced expression of SOD2 in the ischemic CA1 pyramidal neurons by IPC is related with neuroprotective effect through Trx2 against oxidative stress induced by ischemia‐reperfusion injury.…”
Section: Discussionsupporting
confidence: 54%
“…Some papers have shown that the treatment of exogenous Trx increases expressions of both SOD2 mRNA and its protein level in epithelial cells of the human lens and in microvascular endothelial cells in the human lung . Furthermore, we recently reported that the maintenance or increase of endogenous SODs was closely related with protective effects against ischemia‐induced neuronal death in the gerbil hippocampus . With these findings, therefore, we strongly suggest that the enhanced expression of SOD2 in the ischemic CA1 pyramidal neurons by IPC is related with neuroprotective effect through Trx2 against oxidative stress induced by ischemia‐reperfusion injury.…”
Section: Discussionsupporting
confidence: 54%
“…[ 32 ] In addition, we demonstrated that the maintenance or increase of intracellular antioxidant enzymes by the administration of some traditional medicinal plant extracts is closely associated with protective effects against ischemia-induced neuronal death in the gerbil hippocampal CA1 region. [ 17 33 34 ] Therefore, it could be postulated that higher and maintained expressions of intracellular antioxidant enzymes in ischemic neurons after treatment with some extracts may be related with neuroprotective effects against ischemic damage.…”
Section: Discussionmentioning
confidence: 99%
“…It is, thus, applied for gastric pain and distended abdomen. Neuro-protection effect of A. katsumadai for ischemic damage has been observed through antioxidants [1,2]. Choi et al [3] showed that extracts of A. katsumadai attenuate phenylbenzoquinone-induced writhing and carrageenan-induced hyperalgesia, and they found that this effect was independent of opioid receptor but involved in COX-2 pathway, suggesting potential role of A. katsumadai on inflammatory nociception.…”
Section: Introductionmentioning
confidence: 99%